2020
DOI: 10.31235/osf.io/4v86u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global images in a catnet approach: how Greeks and Hungarians see themselves and others

Abstract: The paper presents an attempt to study national-ethnic images and cultural distances with a new conceptual approach and a revival of the Buchanan–Cantril-technique utilizing contemporary network methodology. The conceptual framework related to cognitive maps derived from perceived attributes of other nations and their own called for a renewed application of the catnet concept introduced by Harrison White. Our survey took place in 2016/17, administered online in a joint project with samples of Greek and Hungari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our research revealed that the topics which prevailed in the 2015 Greek political public discourse were the debt crisis and the 'refugee crisis.' The detailed reconstruction of the related processes indicated that the initial prevalence of topics was connected to the debt crisis, and that a change took place with a surge of the 'refugee crisis' in August 2015 (Fokas et al, 2021). Some lessons from these previous studies may provide an introductory view of the settings that surrounded the present research.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our research revealed that the topics which prevailed in the 2015 Greek political public discourse were the debt crisis and the 'refugee crisis.' The detailed reconstruction of the related processes indicated that the initial prevalence of topics was connected to the debt crisis, and that a change took place with a surge of the 'refugee crisis' in August 2015 (Fokas et al, 2021). Some lessons from these previous studies may provide an introductory view of the settings that surrounded the present research.…”
Section: Introductionmentioning
confidence: 77%
“…7 in this volume), public claims-making in Greece turned towards the migration issue somewhat later than in other parts of Europe. Our related analysis of online contents (Fokas et al, 2021) indicated the parallel domination of two topics in the Greek public discourse: the debt crisis and the refugee crisis, with a shift from the former to the latter beginning in August of 2015. The analyses related to the Hungarian media revealed the domination of the political discourse by the 'refugee crisis' in 2015, heavily impacted by xenophobic anti-immigrant propaganda messages.…”
Section: Related Research and Conceptual Literaturementioning
confidence: 95%